FRAGMENTATION IN MACEDONIAN TRADITIONAL ARCHITECTURE IN RELATION TO THE WOOD AS A STRUCTURAL ELEMENT - Temelkovski, Branko (Innovation in Woodworking Industry and Engineering design, 2024)
century. The limitations imposed by specific materials and technological constraints during that era stimulated the development of intelligent and versatile spatial models. Among the defining features of that architecture is the intricate use of wood as a primary constructional element. This research seeks to investigate the qualities of fragmentation of the form and their practical application. The study will commence by defining the concept of fragmentation as a fundamental aspect of architectural expression. It will then systematically analyze its physical and formal properties from various aspects such: materials, spatial structure, construction, grouping of window openings. It will also analyze aspects of human experience and perception, evident through: perception and experience, identity, functionality. The study will examine approximately 200 houses from this period.